Cell specific expression of human Bruton's agammaglobulinemia tyrosine kinase gene (Btk) is regulated by Sp1- and Spi-1/PU.1-family members. - Müller, S; Sideras, P; Smith, C; Xanthopoulos, K (1996)
Bruton's agammaglobulinemia tyrosine kinase (Btk) is a cytoplasmic tyrosine kinase involved in the human disease X-linked agammaglobulinemia (XLA). The gene is expressed in all hematopoietic cells with the exception of T-cells and plasma cells. For this expression pattern the first 280 bp upstream of the major transcriptional start site seems to be sufficient. In vitro footprinting analysis within this part of the promoter revealed two Sp1 binding sites as well as a PU-box. The transcription factor Spi-1/PU.1 as well as the closely related factor Spi-B bound to the PU-box in B-cells. In the erythroleukemia cell line K562, due to the absence of Spi-B, only PU.1 bound to the Btk promoter. Mutation of either site reduced the expression in transient transfection experiments. However, mutation of the PU box had no effect in the T-cell line Jurkat, where none of the Spi-1 family members is expressed. In addition Spi-B as well as PU.1 were able to transactivate Btk expression. In fetal liver of PU.1-/- mice, which lack lymphoid and myeloid cells, expression of Btk was reduced two- to threefold but not abolished. Collectively this study shows that expression of the Btk gene is regulated by the combined action of Sp1- and PU.1-family members.